2016
DOI: 10.17795/ajmb-34014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Three Months of Resistance Training on TCF7L2 Expression in Pancreas Tissues of Type 2 Diabetic Rats

Abstract: Background: Resistance exercise is recommended as a useful therapeutic tool for the treatment of type 2 diabetes (T2D); however, the frequency of studies is inadequate to establish the precise mechanisms of any association between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Then type 2 diabetes was induced by intra-peritoneal injection using nicotinamide injection at a dose of 110 mg / kg body weight and streptozotocin at a dose of 60 mg / kg in diabetic groups. One week after diabetes induction, fasting blood glucose and glucose levels between 150 and 400 mg / dL were considered as a measure to ensure that mice were diagnosed with type 2 diabetes (18). Before applying the training program to homogenize the two training and the control groups, measurement was done using a weighing scale for Japanese animals (accurately 0.01 g).…”
Section: Methodsmentioning
confidence: 99%
“…Then type 2 diabetes was induced by intra-peritoneal injection using nicotinamide injection at a dose of 110 mg / kg body weight and streptozotocin at a dose of 60 mg / kg in diabetic groups. One week after diabetes induction, fasting blood glucose and glucose levels between 150 and 400 mg / dL were considered as a measure to ensure that mice were diagnosed with type 2 diabetes (18). Before applying the training program to homogenize the two training and the control groups, measurement was done using a weighing scale for Japanese animals (accurately 0.01 g).…”
Section: Methodsmentioning
confidence: 99%
“…The role of transcription factors such as FTO, FOXO1, IRS-1, PPARgama, and GLUT4 in insulin-dependent glucose transport has been previously reported (8,10,11,14). In this regard, the PTP1B gene is of particular importance (8) as some researchers have identified it as a regulator of insulin function in mammals and a pharmacological target in T2D (1). It is worth mentioning that the findings of the present study indicated a decrease in blood glucose and insulin resistance levels along with a decrease in PTP1B expression in gastrocnemius muscle in response to interval training in T2D rats.…”
Section: Discussionmentioning
confidence: 49%
“…Although T2D is a multifactorial disease, one of its prominent risk factors is the prevalence of obesity. Consideration of obesity as one of the most important factors contributing to the development of T2D has been supported by some previous studies (1,2).…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations